Pemberdayaan Masjid Melalui Kegiatan TPA dan Bimbingan Belajar Kepada Masyarakat Di Kelurahan Kemlayan Tahun 2022 - Indah Nurhidayati; Delvy Sofiana (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
At this time there are still many people who think that education can only be obtained through school. Such an image is not completely wrong. Because until now there are still many people who depend on getting education services through schools, so that a kind of opinion is formed that education is identical to school. The lack of interest in urban communities to include their children in studying at the TPA arises due to many factors. It is not uncommon for parents to be reluctant to include their children in attending TPA education because parents think that TPA education only interferes with their children's school activities or learning. Moreover, the tendency of people to prioritize formal education.